The age of the Gura Șoimului formation from the Pleșu anticline (Moldavian Subcarpathians, Romania) based on paleoichnology (Geo-Eco-Marina, 2019)
The presence of Mammillichnis ichnogenus in the Gura Șoimului Formation, cropping out in the Pleșu Anticline axis, represents the first paleoichnological argument that confirms the Early Miocene age of this unit. This argument broadens the distribution areal from Vrancea half-window at south, to Bistrița half-window at north. The regional expansion of Arthrophycus (=Sabularia) paleoichnocenosis, which is often associated with Mammillichnis, indicates that the Gura Șoimului Formation has the same age with Vinețișu and Podu Morii units located on the external flysch of the Eastern Carpathians (i.e., Tarcau and Vrancea nappes). Based on the paleoichnological content, the Almașu Formation (=Almașu Sandstone) does not represent the stratigraphic equivalent of the Gura Șoimului Formation; the Almașu Sandstone ichnofauna is continental, while the Gura Șoimului Formation ichnofauna is marine.
Keywords: Mammillichnis; trace fossils; Gura Șoimului Formation; Pleșu Anticline; Subcarpathian Nappe